Religiosity, Health and Participation in Sport - Mohibullah Khan Marwat; Samera Saman; Huang Liang (The Sky, 2024)
This research study was conducted to evaluate and review the existing literature encircling the ambit of religion with reference to participation in sports and health from the psychological perspective. Religion and humans have long been associated and religion has been playing very prominent role in the everyday lives of human beings. Internal peace, eternal satisfaction and contentment are the associated outcomes of attachment with the religion particularly in the event of negative and stressful circumstances. A number of studies endorse the relationship between religion and positive mental and physical health. Literature encircling sports psychology suggests that religious trend of the player can have positive effect upon the overall mental health and performance of the player. Religious practices and gestures in shape of praying are the routine activities particularly before and during competition, among the athletes representing different religious schools of thoughts. Relationship of religiosity and sports have also been looked into from the historical perspectives and one thing became clear that, in the ancient days, sports activities were performed as a part of religious rituals and faith obligatory practices to please their gods/goddesses. Sport activities like running, jumping, boxing, bow-shooting, fighting, javelin throw, discus throw and wrestling had been used to be performed as a sacred religious duty on special periodical ceremonies conducted regularly. Findings of the different studies show that religiosity plays significant role in averting the stressful situation, coping sports related anxiety of the participants and enhancing confidence and self-esteem of the player.